1985
DOI: 10.1159/000176982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soybean Crude Fiber on the Concentrations of Serum Lipids and Apolipoproteins in Hyperlipemic Subjects

Abstract: Effect of soybean crude fiber on the concentrations of serum lipids and apolipoproteins in hyperlipemic subjects was examined. The concentrations of serum triglycerides, VLDL triglycerides and VLDL cholesterol were decreased significantly following the administration of soybean crude fiber for 2 months. Neither were significant changes found in total cholesterol, LDL cholesterol, HDL cholesterol, apo A-I, apo A-II, apo C-II and apo B levels, nor in body weight before and after the administration of soybean cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

1988
1988
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
1
1
1
Order By: Relevance
“…Oat bran and soya-bean fibre have repeatedly been shown to exert hypocholesterolaemic effects (Chen et a/. 1981 ;Anderson et al 1984;Sasaki et al 1985;Lo et al 1986). The results of the present experiment support these former findings ( Table 3 ) .…”
Section: Discussionsupporting
confidence: 88%
“…Oat bran and soya-bean fibre have repeatedly been shown to exert hypocholesterolaemic effects (Chen et a/. 1981 ;Anderson et al 1984;Sasaki et al 1985;Lo et al 1986). The results of the present experiment support these former findings ( Table 3 ) .…”
Section: Discussionsupporting
confidence: 88%
“…The lack of an SDF effect on lipids in the present study may be due, in part, to the normal range of lipid levels of the participants in this study (Table 1). In contrast to these finding, other studies have shown reduced blood lipid levels in hyperlipemic subjects given crude soybean fiber [8,24]. This study shows that the effect of fiber on the plasma glucose level depends on the form in which the fiber is consumed.…”
Section: Discussioncontrasting
confidence: 61%
“…The method of processing appears to be important both for the protein (Van Raaij et aI., 1982) and for the fibre effects. A soya bean "crude fibre" preparation, containing 33% dietary fibre did not lower plasma cholesterol in subjects with mildly elevated cholesterol (Sasaki et al, 1985). In 1983 two groups reported on different concentrated soya cotyledon fibre preparations (Schweizer et aI, 1983;Tsai et aI., 1983).…”
Section: Legumesmentioning
confidence: 99%